Evaluation of Anti-Microbial, Antioxidant and Antiinflammatory Effects of Roghane Khas - Chathumika, L.A.D.D.; Paranagama, P.A.; Herapathdeniya, S.K.M.K. (Faculty of Indigenous Medicine, University of Colombo, 2024)
Antimicrobial resistance is a critical global health challenge necessitating new therapeutic agents. This study evaluates the traditional Unani formulation Roghane Khas, composed of Edaru leaves (Ricinus communis), Vara leaves (Calotropis gigantea), Aththana leaves (Datura metel), bee's wax, Girisindura (Red lead), Keppetiya lakada (Resin of Coccus lacca), and sesame oil, known for its antimicrobial, antioxidant, and anti-inflammatory properties. Roghane Khas's antimicrobial efficacy was tested against bacterial strains such as Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Pseudomonas aeruginosa, Streptococcus pyogenes, and Proteus mirabilis, as well as the fungus Candida albicans using the well diffusion method. The antioxidant properties were assessed using DPPH (2, 2-diphenyl-1-picrylhydrazyl) and FRAP (Ferric Reducing Ability of Plasma) assays, and the anti-inflammatory effects were evaluated using the HRBC (Human Red Blood Cell) membrane stabilization method. The results of well diffusion method showed significant inhibition zones ranging from 9.40 ± 1.22 mm to 12.60 ± 1.97 mm and 9.50 ± 1.22 mm to 11.46 ± 1.97 mm for the DCM (Dichloromethane) extraction and hexane extraction respectively, indicating strong antimicrobial activity. The antioxidant assays revealed potent radical scavenging for DCM extract with IC50 value of 12.56 µg/mL while the hexane extract showed moderate activity with an IC50 value of 217 µg/mL and ferric reducing capacities comparable to standard antioxidants. The HRBC membrane stabilization method demonstrated significant inhibition of inflammation, with percentage inhibitions of 61.57% for the DCM extract and 29.96% for the hexane extract and 50.28% for the methanol extract at 1 mg/mL concentration. These findings support the traditional use of Roghane Khas as a multifunctional therapeutic agent. The study concludes that Roghane Khas exhibits potent antimicrobial, antioxidant, and anti-inflammatory activities, highlighting its potential application in modern medicine to combat antimicrobial resistance. Further research is recommended to elucidate the mechanisms and clinical applications of Roghane Khas
Keywords: antimicrobial resistance; raditional medicine; Roghane Khas; antioxidant activity